Social and political participation on the Internet and generational gap - Delfino, Gisela (2018)
Digital media allows the emergence of different activities that provide new ways to participate in social and political life. The Internet allows reaching groups that are normally inactive or less active in conventional or offline forms of political participation. We sought to explore the influence that frequency of Internet connection, Internet social participation and political discussion (talk about politics) have on political participation on the Internet in three different generations (n = 502, age: 18-67). The youngest participants presented a higher frequency of connection and activities on the Internet, while the older generational group exhibited a greater frequency of political discussion. In general , the three variables are relevant to explain political activity on the Internet; however, the weight of each variable is different depending on the generation considered.